The Importance of Farm Animal Health and Natural Behaviors to Livestock Farmers: Findings From a Factorial Survey Using Vignettes - Vigors, Belinda; Ewing, David A.; Lawrence, Alistair B. (Frontiers in Animal Science, 2021)
There is increasing interest in enabling positive experiences, not just minimising negative experiences, to improve the welfare of farmed animals. This has influenced the growth of private agri-food standards and supported arguments to integrate animal welfare into policy on sustainability and climate change. However, much research finds that farmers predominantly focus on the minimisation of negatives (i.e. health issues). This may impact the positioning of farmers within these wider societal debates, affecting their social licence to farm. It is thus important to better understand farmers’ priorities relating to the minimisation of negative factors (e.g. health issues) and the promotion of positive experiences (i.e. natural behaviours). A novel 2x2 factorial survey using vignettes, which experimentally manipulated health (health issues minimised/not minimised) and natural behaviour (natural behaviours promoted/not promoted) provision, was completed by livestock farmers (n=169), mostly with extensive systems, in the UK and Republic of Ireland. The majority (88%) considered ‘minimising health issues’ to be the most important factor for animal well-being. However, the overall welfare of animals was judged to be highest when both health and natural behaviours were supported. Several individual characteristics, including farming sector, production system, gender, belief in animal mind and business type influenced how participants judged the welfare of animals and the level of importance they gave to health and natural behaviours. Findings suggest that although farmers prioritise the minimisation of health issues they want animals to be both healthy and able to express natural behaviours, and individual characteristics are important for understanding farmers’ welfare-related judgements.